Morsmålsdidaktisk forskning og profesjonalisert lærerutdanning Fem nordiske beretninger om 50 års utvikling og kamp - Erixon, Per-Olof (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
In this book, five experienced Nordic L1-didactitians and teacher educators search for their professional roots as pupils, students, teachers, teacher educators, managers and researchers over a period of fifty years. In the form of the scientific essay, various historical professional struggles and processes that may lie behind this professionalisation are examined, partly from a critical perspective: Academisation, theorising, didacticisation, textualisation, and internationalisation, especially within first language (L1), L1 didactics and L1 didactic research. Documentation and discussion of the complex relationship between institutionalised academic operations and personal and collective knowledge development nevertheless constitute a main line in the presentation. The L1 subjects in which the descriptions are anchored are Danish, Finnish Swedish, Norwegian and Swedish. The contributions provide personal, experience-based, historical representations of the development contextualized with the narrators' own research in the field as well as descriptions of general development trends within schools, education, and society. A framing chapter provides methodological and theoretical premises for the texts and a concluding chapter analyses the content of and discusses the outcome of the essays. The book is aimed at anyone who is interested in the development of professional teacher training on a Nordic basis, especially native language and subject didactics. Although Per-Olof Erixon and Sigmund Ongstad are editors, the book has been created in close collaboration with the other contributors, Sven-Erik Hansén, Ellen Krogh, and Jon Smidt.